PENERAPAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PENCURIAN SEPEDA MOTOR DI WILAYAH HUKUM POLSEK KUTA UTARA - I Nyoman Suryana (Universitas Mahendradatta, 2026)
In essence, resolving criminal acts based on restorative justice at the police level involves a legal product in the form of a settlement carried out in the form of a termination of the investigation and inquiry, or the issuance of an SP3 (Investigation Termination Order), on the grounds that the perpetrator and victim have agreed to reconcile regarding the crime committed. Or, through a peace agreement letter signed by the parties. Restorative justice settlement at the police level is carried out with material and formal requirements. This is regulated in Articles 5 to 6 of Police Regulation Number 8 of 2021 concerning Handling Criminal Acts Based on Restorative Justice.